Gestión presupuestaria de obras en el Gad Parroquial de Pimocha en el periodo 2022. - Herrera Sandoya, María Nicol (2023)
This case study begins with the statement of the problem about the budgetary management of works in the Parish GAD of Pimocha in the period 2022, in the public sector it is important to plan activities through an Annual Operating Plan (POA), who are responsible for making the budget for this plan is the Parish Board, composed of members of the Parish GAD. This research focused on analyzing the budget documents of the income and expenses of the GAD during 2022 and why there were unfinished works during that period, where it was stated that the previous administration did not make adequate arrangements with the Prefecture and the Municipality. With the qualitative and quantitative research methodology, it was possible to extract information provided by the GAD, also a questionnaire was used where through the interview it was possible to have information about the works executed in the year 2022. Through this analysis it can be seen that the variations in the budget of the Parish GAD of Pimocha have prevented the works presented in the POA from being fulfilled.